Anatomical Variation of the Human Superficial Palmar Arch: a Cadaveric Study - Pradhan, Allin; Chalise, Usha; Dhungel, Shaligram (Nepal Medical College Journal, 2025)
Superficial palmar arch is the main arterial supply of palm and formed by the superficial terminal branch of ulnar artery and superficial palmar branch of radial artery. Coleman and Anson, classified the superficial palmar arch (SPA) in two groups, Group I and Group II. Group I, complete arch which is further divided into five types as A, B, C, D and E. Group II, incomplete arch, which is further divided into four types as F, G, H and I. Therefore, the aim of this study was to demonstrate anatomical variation of the human superficial palmar arch in human beings taking examples from cadaveric study. In the present study 50 embalmed cadaveric upper limbs of both side were dissected over a period of one year available in the Department of Human Anatomy, Nepal Medical College, Kathmandu, Nepal. The complete type of SPA according to Coleman and Anson classification was found in 48 (96.0%) hands and incomplete types of SPA was found in 2 (4.0%) of the hands. Two subgroups were observed in the complete SPA group: Type A - formed by the ulnar artery and the superficial branch of the radial artery was observed in 41 (82.0%) hands. Type B - formed by ulnar artery was seen in 7 (14.0%) hands. One subgroup of incomplete Type G - was found in 2 (4.0%) hands. This study provides details about the anatomical variations of superficial palmar arch in humans which aims to be enlightening for the operating hand surgeons and orthopedicians.